Ameliorative and Exacerbating Effects of [pGlu4,Cyt6]AVP(4-9) on Impairment of Step-Through Passive Avoidance Task Performance by Group II Metabotropic Glutamate Receptor-Related Drugs in Mice - Tomoaki Sato; Takayuki Ishida; Koh-ichi Tanaka; Yoshiko Ohnishi; Masahiro Irifune; Tamotsu Mimura; Takashige Nishikawa (Elsevier, 2005)
To examine the effect of the arginine-vasopressin fragment, [pGlu4,Cyt6]AVP(4-9) (AVP4-9), on group II metabotropic glutamate receptor (mGluR2/3) agonist and antagonist induced impairment of passive avoidance (PA) task performance, AVP4-9 or phorbol 12-myristate 13-acetate (PMA) was administered in the presence of mGluR2/3-related drugs that induced the impairment of the step-through-type PA task performance. The PA task performance was evaluated in terms of the latency (the time that elapsed prior to entry into the dark compartment) at 24 h after the electrical stimulation. The subcutaneous injection of AVP4-9 at 1 μg/kg had the greatest facilitative effect on the performance, and the facilitative effect of AVP4-9 was inhibited by NPC-15437, a specific protein kinase C (PKC) inhibitor. The injection of AVP4-9 ameliorated PA task performance impairment induced by DCG-IV, an mGluR2/3 agonist. Intracisternal injection of PMA, a PKC activator, also ameliorated the DCG-IV-induced impairment. High doses of AVP4-9 exacerbated the PA task performance impairment induced by LY341495 (an mGluR2/3 antagonist), and PMA injection (1 μg) also exacerbated the impairment induced by the antagonist. These results suggest that an increase in the activity of the PKC-signaling pathway may not always facilitate PA task performance; therefore, AVP4-9 can either enhance or inhibit memory performance in mice. Keywords:: memory, [pGlu4,Cyt6]AVP(4-9), protein kinase C